Miskonsepsi Pemahaman Materi Bangun Datar Dengan Penerapan Teori Polya di PGMI 3 UINSU - Siregar, Nurhaliza Ertays; Wandini, Rora Rizki (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Misconceptions or misunderstandings can occur due to additions or deletions of what is inherent in the concept. Misconceptions can cause misunderstandings that cause difficulties for students in understanding the learning process. The aim of this research is to identify several misconceptions that occur among PGMI 3 UINSU students regarding the application of polya theory to plane material. The type of research used in this research is qualitative descriptive research in the form of a test on completing students' mathematics results accompanied by interviews related to flat shape material with the application of polya theory. The results of this research show that there are several misconceptions, namely not including the name of the flat figure in the problem, not giving cm marks for the base and height units, and the planning stage of the formula used being incomplete, not making polya theory steps in working on the problem and not evaluating final results or not writing conclusions. This is because students are not used to writing conclusions and also assume that the final calculation result obtained is the solution to the problem. The type of error found in question number 1 is 31.5% and in number 26.2%. From 39 students, a sample of 19 students was taken. 8 students answered the questions correctly and 11 students made mistakes. It is hoped that this misconception will not happen again to other prospective teacher students.